El derecho a la salud de las personas privadas de libertad en el centro de rehabilitación social de varones de la ciudad de Ibarra - Benítez Toapanta, Jefferson Olmedo (2023)
The Ecuadorian Constitution Comprehensive Criminal Organic Code (2014), and international regulations enshrine specific rights despite the restriction of their rights to freedom, resulting from the criminal sentences they serve, however, the reality is not what was expected, the rights Persons Deprived of Liberty (PPL), are violated due to the existence of material conditions contrary to the enjoyment of their basic rights. Thus, this article points out the main findings of the research carried out between 2019 - 2020, at the Social Rehabilitation Center of the city of Ibarra, whose objective focused mainly on investigating overcrowding and its relationship with the constitutionally guaranteed right to health, determining the real situation of protection or violation of the right to health\; Two sources of information were processed and the following methodologies were used: qualitative based on interviews with Rehabilitation Center Authorities and legal professionals\; However, it had a quantitative analysis phase based on the processing of data collected in 2019\; surveys of 150 Prisoners. The results of which were treated descriptively in order to produce an analytical synthesis and graphic representation of the observed data, products of the study. Based on the diagnostic results, we seek to envision strategies leading to suggesting actions and encouraging a local public policy that ensures compliance with the right to health of the PPL. It is concluded that the Ibarra Rehabilitation Center presents poor performance in the treatment of the crisis of prison overcrowding, exceeding its installed capacity by 135%, the health problems associated with overcrowding, sanitation, nutrition, among others, are: respiratory, gastrointestinal, psychological and exacerbation of chronic diseases, leaving the right only in writing, not fulfilled by the State.